Evaluation Of A High Performance Liquid Chromolography (Hplc) Mehtod For Amino Acid Analysis In Feed With Precolumn Derivatization And Fluorescence Detection - Khaleduzzaman, ABM; Khandaker, ZH; Khan, MSH; Banu, LA; Khan, MKA (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted to determine the amino acids content in wheat sample which is often used as internal check in animal feed analysis by pre-column derivatization method using ortho-phthaldialdehyde (OPA) and betamercaptoethanol followed by high-performance liquid chromatography (HPLC). Fluorescence detection was used for the assay of OPA derivatives of amino acids with the detection wavelength set at Ex 340 nm and Em 455 nm. Ortho-phthaldialdehyde reagent itself does not fluorescence and hence produces no peak on the chromatogram and also produces a very low level of background noise. From standard amino acid mixture fourteen amino acids (Asp, Glu, Ser, Gly, Thr, Arg, Ala, Tyr, Met, Val, Phe, Ile, Leu, and Lys) were separated in 55 min with fine resolution. Good reproducibility and accuracy of the method were demonstrated by the determination of amino acids in wheat sample. The precision for the retention time of amino acids (n = 10 injections over 3 days) between the days showed average standard deviation (SD) of 0.43 and coefficient of variation (CV) of 3.32%. The average SD and CV of peak area repeatability over n = 10 injections were 0.72 and 14.93% also indicated the higher sensitivity of the method. The results of the amino acids in wheat samples suggested that the method can be potentially applied for the determination of amino acids in wheat as well as other cereal feeds used in animal diets. DOI: http://dx.doi.org/10.3329/bjas.v37i2.9883 BJAS 2008; 37(2): 66-73